Intrinsic GABAergic system of adrenal chromaffin cells. - Kataoka, Y (1984)
Histochemical and biochemical studies demonstrate that gamma-aminobutyric acid (GABA), glutamic acid decarboxylase (EC 4.1.1.15), and GABA aminotransferase (EC 2.6.1.19) are present in bovine adrenal chromaffin cells. Moreover, [3H]GABA can be taken up and stored by primary cultures of adrenal chromaffin cells. Nicotinic receptor stimulation or KCl depolarization releases the [3H]GABA taken up by these cell cultures. GABA and benzodiazepine recognition sites located in chromaffin cells interact with each other with modalities similar to those described for GABA and benzodiazepine recognition sites located in synaptic membranes prepared from brain tissue. Bicuculline facilitates the release of catecholamine from chromaffin cells induced by nicotinic receptor stimulation but it fails to influence the release of catecholamine evoked by K+ depolarization. Since the GABA-benzodiazepine receptor system appears to modulate nicotinic receptor function, it is suggested that GABA transmission might participate in modulating responsiveness of chromaffin cells to incoming cholinergic stimuli.